EPIDURAL BLOOD PATCH PADA POST DURAL PUNCTURE HEADACHE (PDPH) - Rialta Hamda; Annisa Lidra Maribeth (Nusantara Hasana Journal, 2023)
Post dural puncture headache (PDPH) is a complication that can occur following diagnostic lumbar puncture, spinal anesthesia, and accidental dural puncture during epidural anesthesia. Spinal and epidural anesthesia are important modalities for an anesthesiologist. Anesthesiologists play a role not only in treating the patient, but also in preventing or reducing the risk of PDPH events. This case report presents a case of PDPH which treated by conservative method, continued by Epidural Blood Patch, and the case was followed until the patient recovered.